2016
DOI: 10.1242/dev.130906
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic diversification through transcription factor-mediated suppression of alternative morphologies

Abstract: Neurons display a striking degree of functional and morphological diversity, and the developmental mechanisms that underlie diversification are of significant interest for understanding neural circuit assembly and function. We find that the morphology of Drosophila sensory neurons is diversified through a series of suppressive transcriptional interactions involving the POU domain transcription factors Pdm1 (Nubbin) and Pdm2, the homeodomain transcription factor Cut, and the transcriptional regulators Scalloped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 89 publications
(112 reference statements)
0
41
0
Order By: Relevance
“…Here, we applied multi-spectral, high-speed, volumetric Swept Confocally Aligned Planar Excitation (SCAPE) microscopy [9,10] to characterize the dynamics of neuronal activity in crawling Drosophila larvae. We focused on the Drosophila multidendritic (md) neurons, which are located just within the larval body wall and innervate connective tissues [11,12], the epidermis [13,14] and internal nerves [15]. A subset of six md neurons ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we applied multi-spectral, high-speed, volumetric Swept Confocally Aligned Planar Excitation (SCAPE) microscopy [9,10] to characterize the dynamics of neuronal activity in crawling Drosophila larvae. We focused on the Drosophila multidendritic (md) neurons, which are located just within the larval body wall and innervate connective tissues [11,12], the epidermis [13,14] and internal nerves [15]. A subset of six md neurons ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A subset of six md neurons ( Fig. 1a) extend axons to more dorsal neuropil regions important for motor control, suggesting that they are proprioceptors that provide feedback on body position [15][16][17][18]. This feedback is thought to be particularly important during crawling, which involves periodic strides driven by segmental muscle contractions progressing from posterior to anterior along the body [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, we discovered that PRC2.1 did not directly bind to neuronal genes in these cells and that, instead, it targeted transcription factors involved in sensory neuron development, synaptic function, and axon targeting. Specifically, on a high sugar diet Pcl binding was increased at the cad , GATAe , nub/pdm , Ptx1 loci and decreased at the Scro locus, with corresponding changes in the mRNA levels of these genes ( Interestingly, several of the transcription factors we identified -Ptx1 , Scro , and nub/pdm -have been shown to control the proper branching, synaptic connectivity, and function of sensory neurons (Corty et al, 2016;Iyer et al, 2013;Neumann and Cohen, 1998;Parrish et al, 2006Parrish et al, , 2007Vorbrüggen et al, 1997;Zaffran et al, 2000) , while others ( cad , nub/pdm ) play a role in neuroblast development (Doe, 2017;Kohwi and Doe, 2013) ; PRC2 also functions as a competence factor in neural proliferation, differentiation and sensory neurons (Bahrampour et al, 2019;Doe, 2017;Parrish et al, 2007) . Importantly, we found that the 4 activators that are repressed by Pcl in the high sugar condition are enriched in the Gr5a+ cells on a control diet, while Scro is depleted.…”
Section: Discussionmentioning
confidence: 90%
“…Regulatory mechanisms must ensure that expression levels remain within a narrow range for days and even years while providing robustness against acute perturbations caused by activity and environment. In some cases, the transcription factors that dictate cell type-specific expression levels have been identified (Corty et al, 2016), but how these regulatory inputs are interpreted by DNA elements has not been characterized. Furthermore, it is unclear how transcription factor feedback and cis-regulatory redundancy contribute to ensuring proper expression levels in neurons.…”
Section: Introductionmentioning
confidence: 99%